The Translation of the Work by Ali Münşî of Bursa: Tuhfe-i Aliyye/Kına Kına Risâlesi - Aydüz, Salim; Yıldırım, Esma (Universitas Darussalam Gontor, 2025)
This study examines the historical use of Kına Kına in Ottoman medical practice, focusing on its efficacy, preparation, and associated risks. Drawing on classical medical texts and empirical observations, it explores traditional methods of enhancing Kına Kına’s potency—boiling with mâul-kurah and sweeteners, and later adding çintiyânâ to counter diminishing effects. Although widely used to treat fevers, concerns about side effects such as dizziness and anxiety led to ongoing debates among physicians. A notable 1708 case in Bursa illustrates the dangers of improper dosage. The study underscores the empirical orientation of Ottoman medicine, its commitment to humoral balance, and the cautious but enduring reliance on traditional remedies.